The Implementation of POCA (Reading Corner) Literacy Program to Developed Students’ Vocabulary Mastery and Their Involvement English Learning Process at Fifth Grade of Elementary School - Tata Regita Sherfaty Irawan; Masagus Firdaus; Hanni Yukaman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the implementation of the POCA (Print–Oral–Contextual–Action) literacy program to enhance vocabulary mastery and increase student involvement in English learning among fifth-grade students at SD Al-Fatih Islamic School. Using Classroom Action Research (CAR), the study was conducted in two cycles with a total of 20 students. The program focused specifically on verbs related to daily activities such as waking up, walking, eating, and going to school. Data were collected through vocabulary tests, structured classroom observations, and student interviews. Quantitative findings revealed substantial improvement in students’ vocabulary scores, rising from a mean of 68.4 (pre-cycle) to 76.2 (post-test Cycle I) and 85.6 (post-test Cycle II), with 92% of students meeting the Minimum Mastery Criteria (KKM) set at 75. Qualitative data also showed higher engagement, with students demonstrating active participation and improved confidence in using verbs contextually. These findings suggest that literacy-based learning, particularly the POCA model, is effective because It not only strengthens vocabulary acquisition but also fosters motivation and meaningful involvement in the English learning process.